Reconstructing the infrared spectrum of a peptide from representative conformers of the full canonical ensemble - Amir Kotobi; Lucas Schwob; Gregor B. Vonbun-Feldbauer; Mariana Rossi; Piero Gasparotto; Christian Feiler; Giel Berden; Jos Oomens; Bart Oostenrijk; Debora Scuderi; Sadia Bari; Robert H. Meißner (Communications Chemistry, 2023)
Infrared spectroscopy is widely used for detailed insights into the three-dimensional molecular structure of biomolecules, however, the accurate description of experimental data by theoretical approaches remains challenging due to the dynamic processes that occur in biomolecules. Here, the authors report the accurate interpretation and reproduction of experimental infrared spectra of a model peptide in the gas phase using a combination of replica-exchange molecular dynamics simulations, machine learning and ab initio calculations based on representative structural conformers.